Analysis of research on Korea’s 2015 revised special – Education curriculum - Chang, Ohsun; Jeon, Byungun (Frontiers in Education, 2022)
The purpose of this study was to analyze contents of Korea’s 2015 revised special education curriculum, focusing on papers published in Korean journals and candidate journals from 2016 (i.e., after December 2015 when the 2015 revised special education curriculum was established) to 2022 (present). Future research directions regarding the curriculum are also presented. To this end, this study analyzed 29 academic papers related to the 2015 revised special education curriculum, in line with the purpose of this study. These studies on the 2015 revised special education curriculum were analyzed as follows. First, trends of study purpose had seven subcategories: analysis of curriculum fitness (one paper), curriculum implementation (six papers), exploration of meanings (four papers), analysis of interest (two papers), identification of contents and characteristics (8 papers), development of curriculum elements (one paper), and reconstitution of curriculum (one paper). Second, based on themes, studies were categorized into studies on general guidelines (seven papers) and studies on subject curriculum (20 papers). Based on study results, future curriculum revision and research directions are discussed.